Investigation on willingness of psychiatric nurses to engage in dementia nursing and influencing factors analysis (精神科护士从事失智症护理工作意愿调查及影响因素分析) - GU Liqin (顾丽琴); JI Caifang (季彩芳); TANG Xiaofang (唐晓芳) (Association of Integrative Nursing, 2022)
Objective To investigate the willingness of psychiatric nurses to engage in dementia nursing and analyze its influencing factors, in order to improve the quality of dementia care. Methods Totally 267 registered nurses in Grade 3A psychiatric hospital were investigated by self-made questionnaire, and data was analyzed by fitting a logistic regression model using a statistical package. Results Totally 47(17. 6%) nurses were willing to engage in dementia care. Motivation and interest in dementia care was main influencing factors of willingness to engage in dementia nursing. The main reasons for unwilling to engage in the nursing work of patients with dementia included: difficulty in communication with elderly dementia patients, high nursing risk and high incidence of accidents, complicated physical diseases associated with the elderly, rapid changes in the disease condition, complex illness, lack of professional ability, lack of sense of value and their own development direction, uneven pay and income. Conclusion It is suggested to strengthen the training of psychiatric nurses on dementia related knowledge, theory and care skills, arrange nurses to care for dementia patients, change nurses' cognition of dementia nursing work, strengthen the training of nurses interested in the nursing work of dementia patients, improve their clinical working ability and provide better nursing services for dementia patients. (目的 调查精神科护士从事失智症护理工作的意愿状况, 分析相关影响因素, 以提高失智症照护质量。方法 采用自制问卷调查某三级甲等精神病医院在职注册护士267人, 运用Logistic回归模型分析精神科护理人员从事失智症患者护理工作的意愿现状及影响因素。结果 有17. 6%(47/267)的护士愿意从事失智症护理工作, 对失智症护理工作有兴趣是主要影响因素。不愿意从事失智症患者护理工作的主要原因有: 与老年失智症患者沟通困难、护理风险高及意外事件发生率高、老年人伴发躯体疾病多、病情变化快、病情复杂、自身业务能力不足、没有价值感与自身发展方向不符、付出与收入不平衡。结论 建议加强对精神科护士进行失智症相关知识和理论及照护技能的培训, 有计划安排护士护理失智症患者, 转变护士对失智症护理工作的认知, 加强对失智症患者护理工作感兴趣的护士培训, 提高护士护理失智症患者的临床工作能力。)